Rituximab as first‐line treatment for the management of adult patients with non‐severe hemophilia A and inhibitors. (June 2014) - Lim, M. Y.; Nielsen, B.; Lee, K.; Kasthuri, R. S.; Key, N. S.; Ma, A. D.
Summary Background The role of immunosuppression in the management of patients with congenital hemophilia and inhibitors is uncertain. The use of rituximab has been limited to case reports and case series. In most reports, rituximab was used as second‐line or third‐line treatment following failure of conventional immune tolerance induction therapy, and more commonly in pediatric patients. Objectives The objective of this study was to describe our experience with rituximab for the eradication of factor VIII inhibitors in adult patients with non‐severe hemophilia A. Patients We retrospectively reviewed the medical records of adult patients with non‐severe hemophilia A and a diagnosis of FVIII inhibitor treated with rituximab (four weekly doses of 375 mg m−2) as first‐line treatment at our hemophilia center. Results We identified nine consecutive adult patients with hemophilia A (moderate, n = 5; mild, n = 4) at our institution between 2000 and 2013, with a median age of 54 years (range, 24–77 years) at the time of inhibitor diagnosis. No patient received concomitant immune tolerance induction therapy. All nine patients had successful eradication of FVIII inhibitors. The median time from the first dose of rituximab to a clinical response was 95 days (range, 12–278 days). The median follow‐up was 56 months (range, 13–139 months). Following inhibitor eradication, eight patients were rechallenged with FVIII concentrates. Two patients developed inhibitor recurrence associated with surgery. Conclusion This case series demonstrates that rituximab is a useful first‐line treatment to achieve sustained inhibitor eradication in adult patients with non‐severe hemophilia A.